Sequential catalytic functionalization of aryltriazenyl aldehydes for the synthesis of complex benzenes - Seo, S; Gao, M; Paffenholz, E; Willis, M (American Chemical Society, 2021)
We demonstrate that aryltriazenes can promote three distinctive types of C-H functionalization reactions, allowing the preparation of complex benzene molecules with diverse substitution patterns. 2-Triazenylbenzaldehydes are shown to be efficient substrates for Rh(I)-catalyzed intermolecular alkyne hydroacylation reactions. The resulting triazene-substituted ketone products can then undergo either a Rh(III)-catalyzed C-H activation, or an electrophilic aromatic substitution reaction, achieving multi-functionalization of the benzene core. Subsequent triazene derivatization provides traceless products